Irrigation management based on reference evapotranspiration for pre-sprouted plantlets of sugarcane cultivars - Ohashi,Augusto Yukitaka Pessinatti (2020)
ABSTRACT The pre-sprouted sugarcane plantlets (PSP) system aims the production of healthy and vigorous plants in reduced time, reducing the number of stalks needed for planting. Irrigation is used in all PSP system stages and water management plays an important role. Stage 1 acclimation follows the budding stage and lasts for approximately 21 days. At this stage the plantlets are grown within an agricultural greenhouse to improve initial development. The objectives of this trial were: to identify the irrigation management which results in highest plantlet growth; to evaluate if responses to irrigation management depends on the cultivar; to evaluate water consumption and water use efficiency at early stage under PSP system; and to assess the water management effect on substrate water matrix potential and stomatal conductance in the cultivar IACSP95-5000. The experimental design was a split-plot randomized block design with four replications. Treatments applied in the plots were different irrigation depths based on daily reference evapotranspiration (ETo): 96, 80, 64 and 48%, estimated by Penman–Monteith method. In the subplots, there were sugarcane cultivars IAC91-1099, IACSP95-5000 and IACSP97-4039. Irrigation management based on 80% ETo resulted in higher growth, dry mass accumulation and greater leaf area. Water use efficiency was not influenced by irrigation management. IAC91-1099 presented higher overall growth, leaf area and dry mass accumulation. Water consumption was cultivar-dependent in irrigation managements using 80 and 96% of ETo. Water use efficiency was higher in IAC91-1099 and lower in IACSP95-5000. Lower substrate water matrix potential reduced leaves stomatal conductance, impairing IACSP95-5000 plantlet growth.